Hyperbaric oxygen therapy improves post-concussion symptoms in adults with childhood traumatic brain injury: a retrospective cohort study - Shabi Shlifer, Adi; Suzin, Gil; Shorer, Ran; Lang, Erez; Finci, Shachar; Elman-Shina, Karin; Doenyas-Barak, Keren; Efrati, Shai (Frontiers in Neurology, 2025)
Post-concussion syndrome (PCS) following childhood traumatic brain injury (TBI) can result in persistent cognitive impairments that extend into adulthood, yet it remains significantly underdiagnosed and undertreated. This study evaluated the effects of hyperbaric oxygen therapy (HBOT) on chronic neurocognitive symptoms in adults with PCS stemming from pediatric TBI. We conducted a retrospective analysis of patients treated with HBOT at the “Sagol Center for Hyperbaric Medicine and Research” between 2017 and 2024. Inclusion criteria included TBI before age 17, HBOT initiation after age 20, and the availability of computerized cognitive assessments before and after treatment. All participants received at least 40 sessions of HBOT, consisting of 90 min of 100% oxygen at 2 ATA with air breaks. Twenty-six adults (mean age 31.7 ± 8.6 years) who sustained TBI in childhood (mean age at injury 7.7 ± 5.8 years) met inclusion criteria. Following HBOT, statistically significant improvements were observed in all cognitive domains except for motor skills (global cognition, memory, executive function, attention and information processing speed; all adjusted p < 0.05; effect sizes r = 0.62–0.78, Wilcoxon signed-rank test). These improvements were independent of time since injury (mean 23.6 ± 9.3 years) and initial TBI severity. Notably, individuals with a history of mild TBI exhibited similar impairments and treatment response to those with more severe injuries. These findings suggest that HBOT may induce meaningful neurocognitive improvement even decades after pediatric TBI, supporting its potential role in long-term rehabilitation strategies for this underserved population.